Penerapan Model Cooperative Script untuk Meningkatkan Keterampilan Siswa Membaca Teks Eksposisi - Mardewi, Mardewi; Mansyur, Umar (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the increase in reading ability of exposition texts of Class X students of SMA Negeri 18 Makassar by using the cooperative script model. The type of research used was Classroom Action Research (PTK) which was carried out in two cycles. Each cycle is held in two meetings, including giving tests at the end of each cycle. PTK research procedures in this study include planning activities, implementation of actions, observation, and reflection. The subjects of this study were students of class X SMA Negeri 18 Makassar, which consisted of 35 students. The results showed that the use of the cooperative script learning model proved to be effective in improving students' reading text exposition skills, especially during the activity of finding and searching for the essence of the exposition text, as well as students' enthusiasm and active participation when participating in group discussion activities. The increase in students' reading skills is evidenced by the average score of students in each cycle, which increased by 60% in cycle I, and in cycle II it became 89%. Thus, the application of the cooperative script model is proven to be able to improve the skills of reading expository texts of Class X students of SMA Negeri 18 Makassar. ABSTRAK: Penelitian ini bertujuan mendeskripsikan peningkatan kemampuan membaca teks eksposisi siswa Kelas X SMA Negeri 18 Makassar dengan menggunakan model cooperative script. Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan sebanyak dua siklus. Setiap siklus dilaksanakan sebanyak dua kali pertemuan, termasuk pemberian tes di setiap akhir siklus. Prosedur penelitian PTK dalam penelitian ini meliputi kegiatan perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas X SMA Negeri 18 Makassar, yang berjumlah 35 siswa. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran cooperative script terbukti efektif dalam meningkatkan keterampilan membaca teks eksposisi siswa, khususnya pada saat kegiatan menemukan dan mencari intisari dalam teks eksposisi, serta antusiasme dan partisipasi aktif siswa pada saat mengikuti kegiatan diskusi kelompok. Peningkatan keterampilan membaca siswa tersebut dibuktikan dengan perolehan nilai rata-rata siswa di setiap siklusnya, yakni meningkat sebanyak 60% pada siklus I, dan pada siklus II menjadi 89%. Dengan demikian, penerapan model cooperative script terbukti dapat meningkatan ketarampilan membaca teks eksposisi siswa Kelas X SMA Negeri 18 Makassar.